Konstruksi Opini Publik melalui Media Sosial: Studi Pendekatan Analisis Wacana Kritis Grup Facebook Lintas Kejadian Kota Jayapura pada Bulan Juni 2021 - M. Zaenul Muttaqin; Sriyono Sriyono (Universitas Warmadewa, 2021)
Public opinion has a very strategic function. In a democratic country, public opinion has a dual functions. First, as a mechanism of democratic control. Second, public opinion has function as factors for finding political decisions that answered people's aspirations. The purpose of this study was to explore the Jayapura City Cross-Genesis Facebook group (LKKJ) as a cyberspace that forms public opinion as well as a virtual community. Type of this research is qualitative research. Data analyzed of this research are form of pictures and writings. The secondary data source comes from one of the social media platforms, named facebook group